The nature of the visual discrimination impairment after neonatal or adult ablation of superior colliculi in rats. - Heywood, C; Cowey, A (1986)
The superior colliculi were removed in rats at either one or five days of age or in adulthood. Seven months later they were tested on four successively presented two-choice intensity discriminations. The intensity difference between the discriminanda was reduced across the four problems to encourage choice by comparison. The purpose was to establish whether impoverished scanning is a feature of rats with collicular lesions and whether the age at which the lesion is incurred is important. The number of door-push and approach errors made in reaching criterion were used as measures of performance and the number of head-scans during acquisition was counted. The results provide no evidence that either one- or five-day operated rats exhibit sparing or recovery of the ability to scan discriminanda since all operated animals were impaired. Furthermore, novel retinal projections, present in one-day operated animals, fail to mediate such sparing. Finally, the results did not demonstrate a selective increase in approach errors following collicular lesions and were therefore inconsistent with the view that the impairment is one of visually-guided locomotion. It is concluded that visual discrimination learning is impaired following collicular lesions in circumstances where scanning of discriminanda is required for efficient performance.